Dexmedetomidine to treat opioid withdrawal in infants following prolonged sedation in the pediatric ICU - Tobias, MD, Joseph D. (Journal of Opioid Management, 2006)
This retrospective study aims to report on the use of dexmedetomidine to treat opioid withdrawal following sedation during mechanical ventilation in a cohort of infants. Seven infants in the pediatric intensive care unit of a tertiary care center, ranging in age from three to 24 months (12.4 ± 8.2 months) and in weight from 4.6 to 15.4 kgs (9.9 ± 4.2 kgs), had received a continuous fentanyl infusion, supplemented with intermittent doses of midazolam for sedation, during mechanical ventilation. Withdrawal was documented by a Finnegan score ³ 12. Dexmedetomidine was administered as a loading dose of 0.5 mg/kg/hr, followed by an infusion of 0.5 mg/kg/hr. Dexmedetomidine effectively controlled the signs and symptoms of withdrawal in the seven patients. Subsequent Finnegan scores were £ 7 at all times (median 4, range 1 to 7). Two patients required a repeat of the loading dose and an increase of the infusion to 0.7 mg/kg/hr. These two patients had received higher doses of fentanyl than the other five patients (8.5 ± 0.7 versus 4.6 ± 0.5 mg/kg/hr, p < 0.0005). No adverse hemodynamic or respiratory effects related to dexmedetomidine were noted. This report involves the largest cohort of patients to receive dexmedetomidine in the treatment of withdrawal following opioid and benzodiazepine sedation during mechanical ventilation. We conclude that dexmedetomidine offers a viable option for such issues in the pediatric intensive care unit (PICU) setting.